Fieldwork approaching in socially excluded participants of young neet - Gutiérrez García, Raúl A.; Martínez Martínez, Kalina Isela; Moral Jiménez, María de la Villa; Cudris-Torres, Lorena; González-González, Rogaciano; Paz-Pérez, María Abigail (Gaceta Médica de Caracas, 2021)
This article offers a reflection on how to approach the phenomenon of young people who neither study nor work with the intention of showing an alternative to perform the fieldwork procedure with the support of various qualitative methodological strategies and psychological clinical intervention. El presente artículo ofrece una reflexión de cómo aproximarse al fenómeno de los jóvenes que no estudian ni trabajan con la intención de mostrar una alternativa de realizar el procedimiento de trabajo de campo con el apoyo de diversas estrategias metodológicas cualitativas y para una intervención clínica.